Mechanical Characterization of Banana/Sisal Fibre Reinforced PLA Hybrid Composites for Structural Application - Ranjan, Ravi; Bajpai, P K; Tyagi, R K (Engineering International, 2013)
Advanced technology emergence in the field of petrochemical-based polymers has brought many benefits to mankind. It is validating that the ecosystem is considerably disturbed and damaged as a result of the non-degradable plastic materials used for disposable items. This paper relates the use of hybrid bio-composites, which is eco-friendly and easily degradable. Previous literature related to hybrid bio-composites proves its eco-friendly and excellent degradable properties. In this paper, banana and sisal fibers were selected to execute the hybrid bio-composite preparation with poly lactic as its matrix. Specimens were made with and without fibre treatment and their mechanical properties like tensile, flexural and impact were evaluated as per the standard test procedures. The test results obtained evident that the treated fibers having the best mechanical properties than pure PLA and untreated fibre bio-composites. The chemical treatment also improved fiber matrix interaction by removal of lignin and hemicellulose, which led to the better incorporation of fiber with the matrix. The SEM micrographs of untreated banana/sisal fibre reinforced PLA bio-composites and treated banana/sisal fibre reinforced PLA bio-composites clearly indicated the extent of the fiber-matrix interface adhesion.
Keywords: Banana/Sisal Fibre; Mechanical Characterization; PLA Hybrid Composites; Structural Application